2014
DOI: 10.3324/haematol.2013.096776
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of radotinib in chronic phase chronic myeloid leukemia patients with resistance or intolerance to BCR-ABL1 tyrosine kinase inhibitors

Abstract: ABSTRACTradotinib in Philadelphia chromosome-positive chronic phase-CML patients with resistance and/or intolerance to prior BCR-ABL1 tyrosine kinase inhibitors. (clinicaltrials.gov identifier: 01602952) MethodsAdditional details of the study design and methods can be found in the Online Supplementary Appendix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 37 publications
1
60
0
Order By: Relevance
“…Ponatinib (45 mg once daily) has also been approved by the FDA for patients resistant or intolerant to prior TKI therapy. Also approved, for patients in whom prior TKI therapy fails, are radotinib, which is available in Korea, 110 and omacetaxine, which is a non-TKI drug approved by the US FDA. 111,112 Busulfan is not recommended.…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…Ponatinib (45 mg once daily) has also been approved by the FDA for patients resistant or intolerant to prior TKI therapy. Also approved, for patients in whom prior TKI therapy fails, are radotinib, which is available in Korea, 110 and omacetaxine, which is a non-TKI drug approved by the US FDA. 111,112 Busulfan is not recommended.…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…[1,3,4] Our analytical method was used to measure plasma concentrations of radotinib in its phase 1 and 2 clinical trials. Briefly, the radotinib concentrations in plasma were higher than LLOQ and quantifiable at all the time points.…”
Section: Pharmacokinetic Applicationmentioning
confidence: 99%
“…[1][2][3][4] It is a BCR-ABL1 tyrosine kinase inhibitor with its chemical structure similar to that of imatinib. Recent clinical trials on the efficacy and safety of radotinib in patients with chronic myelogenous leukemia showed that it is effective and well tolerated, with major and complete cytogenetic response rates comparable to those of nilotinib and dasatinib.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between response and logistical organization of CML care is dramatically confirmed by the very low rate of CCyR at 1 year (27/151, or 18%) obtained with imatinib first-line treatment of CP-CML in Ife-Ife, Nigeria (M Durosinmi, personal communication), where important logistical problems (lack of RT-PCR, procurement of drug, power outages, general instability, cultural problems in the acceptance of chronic medical treatment) hampered the efforts of physicians in the past, in addition to the lack of a dedicated CML clinic. Thus the CCyR rates at 12 months show huge variations (Table I), from values close to 90% in recent single center experiences [23,30], to 65-72% in older multicenter registration studies [16,17], to 41% in older population based registries [29], to 18%, using the same drug but in different logistical/management contexts.…”
Section: Type Of Managementmentioning
confidence: 99%